Studying the Optimization, Characterization, and Antioxidant Activities of Phenolic Extracts Extracted from Rhus chinensis Mill. Leaf using Microwave-assisted Extraction System with Glycerol as a Green Solvent - Supjaroenporn, Chalisa; Khongcharoen, Prapawarin; Myo, Hla; Khat-udomkiri, Nuntawat (Current Bioactive Compounds, 2024)
Background: The leaves of Rhus chinensis Mill., a common deciduous tree found in the mild temperate zone of Asia, have many medicinal effects, including antioxidant properties. Objectives and Methods: This study aims to optimize the conditions for extracting phenols from Rhus chinensis Mill. (RCM) using a microwave-assisted extraction system with glycerol (MAEG) via response surface methodology (RSM). It also aims to compare the extraction efficacy of decoction and MAEG methods in terms of the bioactive compounds and antioxidant activities of the extracts obtained through them, identify bioactive compounds in both extracts via ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-ESIQTOF- MS/MS), and determine the cytotoxicity and cellular antioxidant activity of MAEG extract. Results: Temperature and glycerol concentration significantly affected the total phenolic content (TPC) of the extracts. The validated value of TPC was 84.11 ± 4.28 mg GAE/g for the sample obtained under the optimal conditions of 12.76 min at 54.08°C and 34.48% glycerol concentration. MAEG extract exhibited higher antioxidant properties compared to the decoction extract. Different phenolic compounds in the extracts were tentatively identified by LC-QTOF. MAEG concentrations from 1 mg/mL to 7.5 mg/mL were considered non-cytotoxic to NIH/3T3 fibroblasts. Furthermore, the cell viability of NIH/3T3 fibroblasts increased after being treated with MAEG extract (from 2.5 mg/mL to 7.5 mg/mL) and subjected to H2O2- induced oxidative stress compared to H2O2 treatment alone. Conclusion: Finally, MAEG can be used as a novel green extraction method for obtaining bioactive compounds for cosmetic and medicinal applications.
Keywords: green solvent